2009
DOI: 10.1080/09602010802296402
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and relatives' experience of difficulties following severe traumatic brain injury: The sub-acute stage

Abstract: The present study aimed to (1) identify the difficulties most frequently reported by individuals with severe traumatic brain injury (TBI) at the time of discharge from a sub-acute rehabilitation brain injury unit as well as difficulties reported by their relatives, (2) compare patients' and relatives' reports of patient difficulties, and (3) explore the role of injury severity, disability and other factors on subjective experience of difficulties. The primary measure was the European Brain Injury Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…In the current study, patients and caregiver ratings were positively correlated with each other, indicating a similar perception of patients’ impairments. This is in contrast to previous studies that have revealed a discrepancy between patients’ and relatives’ view of difficulties (Holm, Schonberger, Poulsen, & Caetano, ; Teasdale et al., ). However, the present study was conducted with a mean time since injury of 26 months, and the time interval since injury is very likely to affect both patients’ and relatives’ perception of difficulties.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, patients and caregiver ratings were positively correlated with each other, indicating a similar perception of patients’ impairments. This is in contrast to previous studies that have revealed a discrepancy between patients’ and relatives’ view of difficulties (Holm, Schonberger, Poulsen, & Caetano, ; Teasdale et al., ). However, the present study was conducted with a mean time since injury of 26 months, and the time interval since injury is very likely to affect both patients’ and relatives’ perception of difficulties.…”
Section: Discussioncontrasting
confidence: 99%
“…[10][11][12] Discrepancy of reporting between individuals with TBI and their significant others has been used by numerous researchers as a proxy to measure reduced self-awareness of deficits following TBI. As noted above, close other reporting is significantly influenced by a range of social and emotional factors, [7][8][9] which questions the validity of using close other reports as a measure of 'true impairment'. Nevertheless, the self-awareness literature provides some important insights relevant to the current study.…”
mentioning
confidence: 93%
“…[5,6] There is a general assumption that close other reports are more reliable indicators of traumatic brain injury (TBI)-related difficulties, particularly in people with moderate to severe injuries who may lack self-awareness. However, research has shown that factors such as close other mood, [7] caregiver strain [8] and time spent with patients [9] are associated with close other reporting. Perhaps due to these above factors, it is possible that individuals with TBI and their close others may not share a common experience or understanding of post-injury neuropsychological changes.…”
mentioning
confidence: 98%
“…Research speci c to TBI identi es subjective factors that appear to in uence patients' objective functional status, including perception of autonomy, 24 "sense of self", 25 depression, 26 self-awareness, [27][28][29] subjective experience of di culties, 30 and self-reported "psychosocial status" 31 (global representation of subjective and objective function). Given this, we assert that patient and family/caregiver experience should guide the development of instruments for assessment of outcomes and post-injury functional status.…”
Section: Introductionmentioning
confidence: 99%